DISTRICTING FOR ROUTING APPLICATIONS FOR DISTRIBUTION AND COLLECTION SERVICES - Bhanderi, Shyam (2014)
Districting is the partitioning a large geographical region into sub areas according to some criteria in order to carry out operations that have to be conducted within the region. Districting problems and models have been developed extensively in literature for various applications such as political applications, sales territory applications, health care applications, school design applications, routing applications for emergency services and routing applications for distribution and collection services. This dissertation will primarily focus on routing applications for distribution and collections services. This aim of this thesis is to provide an overview of different techniques and models that have been developed in the past for the different distribution and collection applications such as road maintenance, waste collection, postal deliveries and parcel services. This thesis will provide an insight on the importance of conducting districting under each application. The main objectives and aims of different districting problems considered by researchers will be closely examined under each application. Districting algorithms, models and procedures used to solve districting problems will be presented for each application and the results obtained from the different solution methods will be discussed. At the end of the dissertation an area for further investigation will be proposed based on the conclusions made after studying the problems in the various applications under the distribution or collection services.